Cost Structure, Land Productivity, and Price Efficiency IN Shallot Farmers’ Income in Brebes - Eva Hazizah; Krisdiana; Agustina (PT. Maju Malaqbi Makkarana, 2026)
This study explored how cost structure, land productivity, and price efficiency shape the income of micro scale shallot farmers in Brebes Regency based on farmers' reported financial experiences and informants' financial narratives. Using an exploratory qualitative approach, data were collected from five shallot farmers, one agricultural extension officer, and one farmer group leader through semi-structured interviews, non-participant observation, and documentation. The data were analyzed through thematic analysis supported by source and technique triangulation. The findings show that reported income is highly vulnerable to variable production costs, particularly labor, seed, and pesticides. Land productivity is closely related to land ownership status and farming scale, while price efficiency is constrained by farmers' weak bargaining position and dependence on intermediaries. Farmers apply adaptive strategies such as delaying sales, drying harvested shallots, and converting part of the harvest into seed stock. However, these strategies are limited by liquidity needs, storage capacity, product quality, and market uncertainty. The study concludes that improving farmers' income stability requires integrated cost control, asset productivity, price information access, post-harvest support, and stronger farmer institutions.